Benjamin Katz : Photographien. - Baselitz, Georg; Cladders, Johannes; Feiereisen, Doris; Langer, Freddy; Lüpertz, Markus; Wiegand, Wilfried; Van Abbemuseum, Eindhoven; Württembergischer Kunstverein, Stuttgart; Kunstverein Frankfurt (Ostfildern-Ruit : Cantz Verlag Ostfildern-Ruit, 1990)
Andre, Carl ; Anselmo, Giovanni ; Armleder, John ; Baldessari, John ; Barth, Cornelia ; Baselitz, Georg ; Baumgarten, Lothar ; Becher, Bernd & Hilla ; Beuys, Joseph ; Bijl, Guillaume ; Bill, Max ; Blume, Bernhard Johannes ; Boltanski, Christian ; Bonvie, Rudolf ; Broodthaers, Marcel ; Buchholz, Daniel ; Buren, Daniel ; Buthe, Michael ; Byars, James Lee ; Bömmels, Peter ; Büttner, Werner ; Caumont, Jacques ; Chillida, Eduardo ; Cremer, Siegfried ; Cucchi, Enzo ; Dahn, Walter ; Damisch, Gunter ; Daniels, René ; Dokoupil, Jiri Georg ; Droese, Felix ; Fabro, Luciano ; Felber, Gina Lee ; Filiou, Robert ; Fischl, Eric ; Fischli, Peter ; Fritsch, Katharina ; Froment, Jean-Louis ; Förg, Gunther ; Gac, Jean Le ; Genzken, Isa ; Gilbert & George ; Goodman, Marian ; Graubner, Gotthard ; Gruber, Fritz ; Haacke, Hans ; Hains, Raymond ; Hamilton, Richard ; Haring, Keith ; Hermanns, Ernst ; Herold, Georg ; Hoet, Jan ; Höckelmann, Antonius ; Immendorff, Jörg ; Judd, Donald ; Katz, Alex ; Katz, Benjamin ; Kelley, Mike ; Kertesz, André ; Kiecol, Hubert ; Kiefer, Anselm ; Kippenberger, Martin ; Kirkeby, Per ; Klapheck, Konrad ; Klauke, Jürgen ; Klein, Astrid ; Knoebel, Imi ; Koberling, Bernd ; Kohlhöfer, Christof ; Kosuth, Joseph ; Kounellis, Jannis ; Lasker, Jonathan ; LeWitt, Sol ; Lefin, Udo ; Leroy, Eugène ; Levine, Les ; Lichtenstein, Roy ; Luginbühl, Bernhard ; Lüpertz, Markus ; Marden, Brice ; Mattner, Jakob ; Merz, Gerhard ; Meuser ; Mields, Rune ; Minetti, Bernhard ; Mucha, Reinhard ; Münch, Horst ; Nitsch, Hermann ; Näher, Christa ; Odenbach, Marcel ; Oehlen, Albert ; Oehlen, Markus ; Oldenburg, Claes ; Paeffgen, C.O. ; Paik, Nam June ; Palermo, Blinky ; Panamarenko ; Paolini, Giulio ; Penck, A.R. ; Poirier, Anne & Patrick ; Polke, Sigmar ; etc.
Benjamin Katz : Photographies, Stedelijk van Abbemuseum, Eindhoven, 16. September - 5. November 1989 / Württembergischer Kunstverein, Stuttgart, 7. Februar - 11. März 1990 / Kunstverein Frankfurt, Frankfurt, 1991
biog., ind. tent. p. 186
Duits
Engels
boek
Keywords: Katz, Benjamin